Improving design and engineering for production that created the resource for sustainable competitive advantage of a Malaysian Naval Shipyard - Jamaluddin, Abdullah (2024)
Malaysia Shipbuilding and Ship Repair (SBSR) industry has been growing steadily, supported by the country’s strategic location, skilled labour, and modern infrastructure. However, the industry is experiencing the problem of poor performance in terms of product delivery. The malfunctioning of Design Engineering For Production (DEFP) is directly linked to the reasons why ship deliveries are delayed. DEFP is developed into a resource that is vital to the performance of the shipyard through transformation drive. The study aims at the context of DEFP as a critical element of change in building company’s strategic resources. Hence, it is crucial to determine how DEFP is influencing the conditions as a strategic resource to gain the sustained competitive advantage of the company. The research used the Resource-based View as the primary model to analyse the resources that are contributing to the sustained competitive advantage position of the Malaysian Local Shipyard (MLS). Data generated in this qualitative study analysed using ATLAS.ti with triangulating method to explain the similarities of phenomenon from the various study methods namely interview observation and documents review. Findings of the research indicate that as a resource DEFP is valuable, rare, imperfectly imitable and with no substitutability. The malfunctioning of DEFP is directly linked to the reasons why ship deliveries are delayed. DEFP is developed into a resource that is vital to the performance of the shipyard through transformation drive. Through the creation of DEFP and continuing development of this resource, the research concludes that DEFP has contributed to the sustained competitive advantage of the shipyard. Study limitations and recommendations for future research are also covered in this study.